Monte Carlo simulation of the dynamic micro-multileaf collimator of a LINAC Elekta Precise using PENELOPE. - González-Infantes, Wilfredo; Lallena, Antonio; Alfonso, Rodolfo (IOP, 2011)
Micro-multileaf collimators are devices that are added to LINAC heads for stereotactic radiosurgery. In this work, the performance of an Elekta Precise LINAC, with a dynamic micro-multileaf collimator manufactured by 3D-Line has been studied. Monte Carlo simulations based on PENELOPE code and measurements with three different detectors (PTW Semiflex 31010 chamber, PTW PinPoint 31016 chamber and PTW Diode 60008) have been carried out. Simulations were tuned by reproducing the experimental TPR20,10 quality index, providing a nice description of both the PDD curve and the transverse profiles at two depths measured. The geometry of the micro-multileaf collimator was tested by calculating the transmission through it and it was needed to reduce significantly the leaf separation indicated by the manufacturer to reproduce the experimental results. An approximate simulation in which the transport of the particles traversing the dynamic micro-multileaf collimator was described in a simplified way was analyzed, providing a good agreement with the full simulations. With the MC model fixed, output factors for various field sizes were calculated and compared to the experimental ones, obtaining a good agreement. PDDs and transverse profiles at two depths measured with the diode for small fields were well reproduced by the simulation, while the measurements performed with the PinPoint chamber showed differences in the PDDs, at large depths, and in the transverse profiles, at the penumbra. Monte Carlo simulations and Semiflex and diode measurements, performed for a 7.0 cm×7.0 cm field, were in nice agreement, while those obtained with the PinPoint chamber showed differences that increased with the depth in water. At the phantom entrance, all measurements showed non-negligible differences what made Monte Carlo a good option to estimate the absorbed dose in this region.
https://publishingsupport.iopscience.iop.org/questions/what-is-iop-publishings-green-open-access-policy/
Keywords: Montecarlo, Método de; Aceleradores lineales; Monte Carlo; LINAC; PENELOPE